STRENGTHENING MSME RESILIENCE IN THE TOURISM SECTOR: A QUALITATIVE STUDY OF POST-PANDEMIC MARKETING STRATEGIES IN INDONESIAN NON-STAR HOTELS - Marhendra, Audio Valentino Himawan; Fauzan, Daffa Abrar Nur (Institut Pendidikan Tapanuli Selatan, 2026)
COVID-19 pandemic severely impacted the global hotel industry, profoundly jeopardizing the operational viability and long-term existence of Micro, Small, and Medium Enterprises (MSMEs). Achieving Sustainable Development Goal (SDG) 8, which focuses on promoting Decent Work and Economic Growth, necessitates the protection and reinforcement of these small firms to guarantee the enduring and comprehensive revival of the tourism sector. This study meticulously examines the strategic alterations in marketing methods employed by Fellas Inn Family Guest House, a non-star hotel MSME situated in Malang, Indonesia, as a dynamic response to the unprecedented challenges posed by the post-pandemic landscape. We utilized a rigorous qualitative case study approach to gather in-depth empirical data through comprehensive semi-structured interviews with management and operational staff, complemented by extensive digital observation. The core findings indicate a critical and necessary strategic pivot: the corporation fully discontinued its traditional reliance on price-based marketing in favor of adopting